ANALISIS PENERAPAN ETIKA ISLAM PADA LAYANAN PERAWATAN WAJAH DI SALON MUSLIMAH RUMAH CANTIK SEHAT MUSLIMAH MALANG - Intan Nisfan Naharo; Mutimmatul Faidah; Octaverina Kecvara Pritasari; dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2025)
This study is motivated by the need of Muslim women for beauty care places that comply with Islamic principles. It aims to analyze the implementation of Islamic ethics in facial care services at Rumah Cantik Sehat Muslimah (RCSM) Salon in Malang, including the facilities supporting the application of Islamic ethics and consumer responses to the services provided. The research objectives are: (1) To understand the implementation of Islamic ethics in facial care services at RCSM Salon Malang, (2) To identify salon facilities that support the application of Islamic ethics at RCSM Salon Malang, (3) To assess consumer responses to the services and facilities at RCSM Salon Malang. The research employs a qualitative descriptive method. It was conducted at RCSM Salon Malang with research subjects including the owner, employees, and customers. Data was collected through observation, interviews, questionnaires, and documentation, with instruments such as observation guidelines, questionnaires, and interview guides. Data analysis was performed using techniques of data reduction, data presentation, and conclusion drawing. The research findings are: (1) RCSM Salon has implemented Islamic ethical principles such as ihsan (optimalism), itqan (precision), honesty, and fairness. (2) Supporting facilities include exclusive spaces for women, halal-certified products, and prayer rooms. (3) Most consumers provided positive feedback on the services, although certain aspects, such as consistency in service time and transparency in service duration, need improvement. The conclusion of this study is that the application of Islamic ethics at RCSM Salon has successfully created services that meet the needs and values of Muslim women customers. Recommendations include enhancing employee training, ensuring service time transparency, and developing products and facilities to maintain competitiveness and service quality.Keywords: Islamic Ethics, Muslimah Salon, Facial Care, RCSM Malang, Sharia Services